Real-life outcomes for oral disease-modifying treatments of relapsing-remitting multiple sclerosis patients: Adherence and adverse event profiles from Marmara University - VURAL, EZGİ; ENGİN, ESİN; SÜNTER, GÜLİN; AĞAN YILDIRIM, KADRİYE; GÜNAL, DİLEK (My University, 2023)
Background/aim: Disease-modifying treatments (DMT) are used to prevent future relapses and disability. High long-term adherence to treatment is important to achieve disease control. This study aims to investigate and compare adherence, adverse event (AE) profiles, and frequencies, main reasons for treatment discontinuation under Teriflunomide (TERI), Dimethyl Fumarate (DMF), and Fingolimod (FNG) for relapsing-remitting MS (RRMS) patients. This study is designed to explore patient-reported experiences in real-life settings. Materials and methods: Patients who were older than 18 years with a definite diagnosis of RRMS and no history of stem-cell transplantation were included. Outpatient clinic data files at the Neurology Department of Marmara University from June 2012 to June 2019 were examined retrospectively. Results: One hundred and ninety MS patients were enrolled. 118 FNG, 51 DMF, 44 TERI treatment cycles were recorded. Time since disease onset, time since diagnosis, and treatment duration were significantly longer for FNG (p = 0.012, p = 0.004, p < 0.001). 72.8% of all the treatment cycles were continued. There was no significant difference in treatment continuity between the 3 DMT groups. The most common reasons for treatment discontinuation in order of frequency were adverse events, the progression of the disease, and the persistence of relapses. No significant difference was found for treatment discontinuation reasons. 32% of the patients reported at least one AE. 28% FNG, 49 % DMF, and 27.3% TERI using patients reported AEs. AEs were much more frequently reported for DMF (p = 0.015). The most common adverse events for each DMT were alopecia (n = 6, 13.6%) for TERI, flushing for DMF (n = 20, 39.2%), and persistent lymphopenia for FNG (n = 9, 7.6%). No severe or life-threatening AE was reported for DMF, one patient experienced pancreatitis under TERI, and 11 (9.3%) patients using FNG had to stop treatment due to serious or life-threatening AEs including cardiac adverse events, opportunistic infections, and dysplasia. Conclusion: Overall treatment discontinuation because of AEs is as low as 10.3% in this study. However, AEs are still the main reason for treatment drop-out.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; adverse event; disease-modifying therapies; Multiple sclerosis; treatment adherence; treatment drop-out